Investigation of Compact Metallic Environments on Power Attenuation and Read Performance of HF RFID - Herrick Han Lin Yeap; Kok Seng Eu; Kian Meng Yap (IEEE Access)
Radio Frequency Identification (RFID) technology has revolutionized inventory management, enhancing tracking efficiency across industries. However, its reliability is significantly compromised in metal-rich environments due to wave reflection, absorption, and signal obstruction, leading to missed reads, reduced detection range, and interference. This study presents a systematic investigation into the detection performance of High Frequency (HF) RFID-tagged inventories stored within confined metallic storage facilities. Specifically, this research examines how metallic environments create RFID interference by altering electromagnetic wave propagation, causing signal distortions, multi-path effects, and unpredictable attenuation patterns. Through simulation and experimentation, we analyze the impact of metallic shelves on RFID performance and explore strategic mitigation techniques, including optimized tag-to-reader placement, antenna configurations, and adaptive scanning methodologies. Our findings reveal unique interference characteristics in different metal scenarios, uncover detection patterns, and form the basis for proposing adaptive methods to enhance RFID readability. The study provides novel insights into optimizing RFID detection in challenging metallic environments and lays the groundwork for future advancements in RFID-based inventory tracking systems.